Factors affecting information technology (IT) competency among auditors in Kedah - PUTRI AMIRAH, MEGAT AZAMUDDIN (2020)
The growth of technological advancement in the way external auditors perform their work has revolutionized. A new detailed range of expertise in information technology combined with the skills of IT and other auditing skills are required to respond to this challenge. This study aims to examine the factors that affecting the information technology (IT) competency among auditors in Kedah. This study was adopting the Competency Theory and Human Capital Theory. The objectives of study are to measure the relationship of training from accounting bodies, organizational support and self-efficacy towards information technology (IT) competency. This study employed quantitative method and targeted respondent were external auditors in Kedah. A total of 97 electronic questionnaires were distributed to participants and 48 responses were returned and usable for further analyses. Collected data were analysed by using PLS-SEM and the results shows that self-efficacy has significantly relationship and contributed to the information technology (IT) competency among auditors in Kedah. However, the study discovered that training from accounting bodies and organizational support were insignificant relationship towards the information technology (IT) competency of the auditors in Kedah. Thus, implications of the findings, potential limitations, and directions for future research were discussed.